How tax audits shape transfer pricing, tax havens, and tax aggressiveness - Nita Andriyani Budiman (Manajemen dan Bisnis, 2026)
This study examines the effects of transfer pricing and tax haven activities on tax aggressiveness, with tax audits serving as a moderating variable. The research focuses on energy companies listed on the Indonesia Stock Exchange during the 2010–2023 period. Using a quantitative approach, this study analyzes 224 firm-year observations and applies panel data regression with Moderated Regression Analysis (MRA). The results show that transfer pricing positively affects tax aggressiveness, indicating that related-party transactions provide opportunities for companies to reduce their tax burden. In contrast, tax haven presence negatively affects tax aggressiveness, suggesting that firms do not primarily utilize tax haven subsidiaries for tax aggressiveness. Furthermore, tax audits weaken the positive relationship between transfer pricing and tax aggressiveness, indicating that stronger tax enforcement reduces opportunistic tax behavior. However, tax audits strengthen the relationship between tax havens and tax aggressiveness. These findings highlight the important role of tax audits in limiting tax aggressiveness and strengthening tax compliance. The study contributes to the tax avoidance literature by providing empirical evidence on the moderating role of tax audits in the relationship between transfer pricing, tax havens, and tax aggressiveness within the context of Indonesia’s energy sector.